ANALISIS PENGARUH COMPANY GROWTH, INVESTMENT OPPORTUNITY SET, ROA, DEBT COVENANT TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Albertho Hendrick Ellyas S; Silvana Pebrina; Risnawati Ziliwu; Mesrawati Mesrawati; Arridho Abduh (JURNAL LENTERA BISNIS, 2025)
This study aims to test and analyze the effect of Company Growth, Investment Opportunity set, ROA, and Debt Covenant on Accounting Conservatism. This study uses a sample of Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) in the period 2020- 2022. The type of data used in this study is Quantitative data, so that during the 3 years of observation there were 78 annual reports analyzed. The analysis method of this study is multiple linear regression. The Adjusted R Square value is 0,175. This shows that 17,5% of the variation of Company Growth, Investment Opportunity Set, ROA, Debt Covenant can explain the relationship between Accounting Conservatism while the remaining 82,5% is explained by other variables such as Cash ratio, Debt to equity ratio, Leverage, Company size and others. The results of this study indicate that Company Growth a partial negative and significant effect on Accounting Conservatism, Investment Opportunity Set partially has no influence an is not significant on Accounting Conservatism, ROA partially has no influence and is not significant on Accounting Conservatism, and Debt Covenant partially Set partially has no influence an is not significant on Accounting Conservatism.